1999
DOI: 10.1161/01.atv.19.4.1026
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Venous Thromboembolism and Clinical Manifestations in Carriers of Antithrombin, Protein C, Protein S Deficiency, or Activated Protein C Resistance

Abstract: Abstract-Deficiencies of antithrombin (AT), protein C (PC) or protein S (PS), and activated protein C resistance (APCR) are very well-established coagulation defects predisposing to venous thromboembolism (VTE). We performed a retrospective cohort family study to assess the risk for VTE in individuals with AT, PC, or PS deficiency, or APCR. Five hundred thirteen relatives from 9 Italian centers were selected from 233 families in which the proband had had at least 1 episode of VTE. We calculated the incidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
107
0
12

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(126 citation statements)
references
References 37 publications
7
107
0
12
Order By: Relevance
“…However, according to a recent study, family history is important in both provoked and unprovoked VTE [6]. This is in agreement with familial studies of defined genetic defects, in which approximately 50% of cases involving a first thrombotic event are unprovoked [35][36][37]. Acquired risk factors are usually not taken into account when considering the overall importance of a family history of VTE [6,41,42], although familial risks have been estimated in unprovoked VTE cases by Couturaud et al [45].…”
Section: Familial History and Unusual Forms Of Vtementioning
confidence: 61%
“…However, according to a recent study, family history is important in both provoked and unprovoked VTE [6]. This is in agreement with familial studies of defined genetic defects, in which approximately 50% of cases involving a first thrombotic event are unprovoked [35][36][37]. Acquired risk factors are usually not taken into account when considering the overall importance of a family history of VTE [6,41,42], although familial risks have been estimated in unprovoked VTE cases by Couturaud et al [45].…”
Section: Familial History and Unusual Forms Of Vtementioning
confidence: 61%
“…Deficiency of AT, PC and/or PS has been consistently linked with venous thromboembolism (VTE) [7]. The large cohort studies have demonstrated increased risk of VTE in asymptomatic individuals with the deficiency of AT, PC and/or PS and positive family history for VTE episodes [7,8].…”
mentioning
confidence: 99%
“…The present patient and his father had suffered repeated and severe thromboembolic events. Furthermore, our patient' s thrombotic onset occurred when he was only 13, while the risk of venous thrombosis in association with protein C or S deficiency increases with age after age 20 (21,22). Combined deficiency of proteins C and S may increase not only the risk of recurrent thromboembolism but also the manifestation of early vascular incidents.…”
Section: Case Reportmentioning
confidence: 70%